Navigating Resistance: The Minangkabau Indigenous Community's Opposition to the Land Certification Program in West Sumatra, Indonesia - Dewi, Susi Fitria; Yulika, Febri; Sulaiman, Nor Lisa; Salleh, Kahirol Mohd; ., Evelynd (Journal of Ecohumanism, 2024)
The customary land certification program, launched in 2016 by Indonesia’s National Land Agency, continues to encounter resistance from certain indigenous communities. This study aims to explore the forms of resistance, the underlying drivers of this opposition, and strategies to address these challenges. Adopting a qualitative descriptive research design and employing a case study methodology, data were collected through in-depth interviews with thirteen informants, field observations, and analysis of relevant documents. The findings highlight three key insights. First, indigenous communities resist the program by refraining from participating, driven by concerns over the privatization of communal land. Second, this resistance is exacerbated by violations of customary practices, particularly the buying and selling of communal land following the issuance of ownership certificates. Third, mitigating this resistance requires a strategic revision of regulations governing the issuance of customary land certificates. The active involvement of local authorities and the integration of indigenous cultural values are critical for ensuring the program's success and fostering broader acceptance of land administration policies. This study underscores the importance of culturally sensitive policy frameworks and collaborative governance in addressing indigenous land rights, contributing to the broader discourse on sustainable land administration in multicultural societies.